Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of clinical management of spontaneous subarachnoid haemorrhage. Issue 4 (18th December 2019) - Dong, Yi; Guo, Zhen-Ni; Li, Qi; Ni, Wei; Gu, Hongqiu; Gu, Yu-Xiang; Dong, Qiang
Abstract : Aim: Spontaneous subarachnoid haemorrhage (SAH) caused by ruptured cerebral aneurysm is a severe subtype of haemorrhagic stroke. Although the incidence of SAH is relatively low among all cerebrovascular diseases, the mortality is the highest. The critical management of SAH is challenging. We provide this evidence-based guideline to present current and comprehensive recommendations for the diagnosis and treatment of non-trauma SAH. Methods: A formal literature search of MEDLINE (1 January 1990–30 June 2019) was performed. Data were synthesised with the use of evidence tables. Writing group members met by teleconference to discuss data-derived recommendations. The Chinese Stroke Association's levels of evidence grading algorithm was used to grade each recommendation. The guideline draft was reviewed by Chinese Stroke Association's Stroke Fellow Committees. It is intended that this guideline be fully updated every 3 years. Results: Evidence-based guidelines are presented for the care of patients presenting with non-trauma SAH. The focus of the guideline was subdivided into transfer and systems of care, diagnosis flowchart, aetiology and differentiation, prevention of rebleeding, surgical and endovascular repair of ruptured aneurysms, management of vasospasm and delayed cerebral ischaemia, management of hydrocephalus, management of seizures and management of medical complications. Conclusions: The guideline offers a framework for SAH management. Early professional and aggressive care of SAH might help dramatically.